Changes in Cardiometabolic Risk Factors Over Two Decades in a Rural Population in Western India - Sindhu Nila; Aditi Apte; Yogeshwar Kalkonde; Dhiraj Aggarwal; Sanjay Juvekar (Indian Journal of Public Health, 2025)
Background: Surveillance and control of cardiometabolic risk factors can be a cost-effective strategy for controlling noncommunicable diseases in resource-limited settings. However, long-term studies on them in rural India are limited. Objectives: The objective of this study was to assess the changes in the burden of cardiometabolic risk factors between the years 2005 and 2022–2023. Materials and Methods: Two cross-sectional studies were conducted in 2005 and 2022–2023 in a well-defined population in the Vadu Health and Demographic Surveillance System in the rural Pune district. Trained surveyors used the WHO STEPS tool to measure tobacco use, alcohol consumption, fruit and vegetable consumption, anthropometry, and blood pressure in both studies. Fasting blood glucose was measured only in the recent study. Both studies used random stratified sampling with 10-year age-sex strata for the 25–64-year age group. Data were analyzed using a Chi-square test and age-adjusted, sex-stratified prevalence rates (n = 2073 [2005]; n = 1711 [2022–2023]). Results: Over 17 years, the age-adjusted prevalence of generalized overweight or obesity has more than doubled (31.6% to 70.1% in men and 22.8% to 60.1% in women). Central obesity prevalence has also more than doubled (20.2% to 54.3% in men and from 21.6% to 45.4% in women). While there has been a decrease in the prevalence of hypertension in both genders (25.9% to 22.1% in men and 22.7% to 17.5% in women), the prevalence of prehypertension has increased (41.6% to 60.1% in men and 32.8% to 43.9% in women). Conclusions: The study suggests the need for primary prevention strategies to control obesity and prehypertension in the study population and similar rural communities in India.